Использование дискретного аналога производной вектора состояний в законе управления при синтезе стабилизирующего управления запасами - Дорофеев, Юрий Иванович (НТУ "ХПИ", 2014)
Рассматривается задача синтеза стабилизирующего управления запасами в условиях действия неизвестного, но ограниченного внешнего спроса и структурных ограничений на значения состояний и управляющих воздействий. Управление строится в виде линейной нестационарной обратной связи с использованием дискретного аналога производной вектора состояний. Для оценивания множества достижимости замкнутой системы применяется понятие инвариантного эллипсоида. С помощью техники линейных матричных неравенств задача синтеза управления сведена к совокупности задач полуопределенного программирования. Рассмотрен численный пример.

The problem of stabilizing inventory control synthesis under the action of an unknown but bounded external demand and structural constraints on the values of states and control actions is consider. Control law is designed as a linear time-dependent feedback using the discrete analogue of the state vector derivative. This control method allows to form the desired dynamic properties of a closed system with incomplete information about the external disturbances. The concept of invariant ellipsoid is used for the evaluation of the closed system reachability set. The control synthesis problem is reduced to a set of semidefinite programming using the technique of linear matrix inequalities. The numerical example is consider. Numerical solution of the problem is obtained by using freely distributed software implementation of methods for solving convex optimization.
The use of discrete analogue of the state vector derivative in the control law at the synthesis of a stabilizing inventory control
Keywords: теория управления; управление запасами; множество достижимости; инвариантный эллипсоид; линейное матричное неравенство; автоматические системы; inventory control; reachability set; invariant ellipsoid; linear matrix inequality; semidefinite programming